Communications and Urban Systems in Mid-Nineteenth Century Canada - Goheen, Peter (Urban History Review / Revue d'histoire urbaine, 1986)
In presenting the results of an analysis of the non-local economic content of the major newspapers published in British North America in 1845 and 1855, this paper offers support for the contention that public communications in the colonies were organized principally so as to secure privileged access to international sources of information, especially from Britain and the United States. The ties linking major colonial cities with international networks were well established by 1845 and preceded the effective organization of communications within the colonies. In 1855, by which time the telegraph was widely available, the importance of American sources of information had increased. By this date there was evidence that at least in Canada West regional communications and markets were becoming better organized. The paper argues that nineteenth-century British American urban communications be approached from the viewpoint of their participation in international rather than exclusively colonial or regional systems.